2011
DOI: 10.3382/ps.2011-01418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo injection of carbohydrates on embryonic metabolism, hatchability, and subsequent somatic characteristics of broiler hatchlings

Abstract: The effects of the in ovo injection of different carbohydrate solutions on the internal egg temperature (IT), hatchability, and time of hatch of embryonated Ross × Ross 708 broiler hatching eggs were determined. In addition, the BW, liver weight, yolk sac weight (YSW), and yolk-free BW (YFBW) of the embryos on d 19.5 of incubation and of the chicks on day of hatch were determined. Eggs containing live embryos were injected in the amnion on d 18.5 of incubation using an automated multiple-egg injector. Solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
4
41
1
1
Order By: Relevance
“…Different results were observed in hatchability with in ovo injection. For example, it has reported that in ovo injection decreased hatchability (Ohta et al, 1999;Zhai et al, 1999;McGruder et al, 2011a) and increased (Ohta et al, 2001;Bottje et al, 2010) and not affected (Zhai et al, 1999;McGruder et al, 2011b). These contradictious results about hatchability might be related with the different injection techniques or injection depths.…”
Section: Resultsmentioning
confidence: 66%
“…Different results were observed in hatchability with in ovo injection. For example, it has reported that in ovo injection decreased hatchability (Ohta et al, 1999;Zhai et al, 1999;McGruder et al, 2011a) and increased (Ohta et al, 2001;Bottje et al, 2010) and not affected (Zhai et al, 1999;McGruder et al, 2011b). These contradictious results about hatchability might be related with the different injection techniques or injection depths.…”
Section: Resultsmentioning
confidence: 66%
“…Furthermore, maternal overnutrition may cause enhanced activities and upregulation of certain enzyme and transporter genes via increasing intestinal functions, while maternal undernutrition caused disturbed fetal intestinal development in newborn pigs (Cao et al, 2014). On the other hand, avian embryos dependent on the nutrients stored in the egg that supplies necessary energy and building blocks for the metabolic activities and growth (Zhai et al, 2011). The in ovo (IO) nutrients of the chick embryo consist mainly of albumin (protein), yolk fat and a trace amount of carbohydrates.…”
Section: Growth and Development Of Skeletal Musclementioning
confidence: 99%
“…The in-ovo method was first used by Sharma & Burmester (1982) for the vaccination of turkey hatching eggs against Marek's disease. Recently, the in-ovo method has been investigated by researchers for administering ascorbic acid (Elibol et al, 2001;Ipek et al, 2004;Sgavioli et al, 2015), carbohydrates (Zhai et al, 2011;Salmanzadeh, 2012;Ipek et al, 2004;Tako et al, 2004), amino acids (Bhanja et al, 2014;Ohta et al, 1999;Kermanshahi et al, 2015), vitamins (Bello et al, 2013;Salary et al, 2014), minerals (Yair et al, 2013;Oliveira et al, 2015), pollen (Coskun et al, 2014), hormones (Moore et al, 1994;Kocamis et al, 1999), and royal jelly (Moghaddam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%